"It's a mass shooting in the hood everyday": Black and Latine youth organizers' reflections on structural racism and community gun violence. - Reed, Taylor A.; Wilf, Sara; Millet, Victoria; Wray‐Lake, Laura (American Journal of Community Psychology, 2025)
This study investigated young Black and Latine organizers' perceptions of how mainstream narratives of gun violence relate to and influence their antigun violence organizing work. We analyzed interview data from 22 Black and Latine young people (Mage = 19.91, 55% women) who were engaged in gun violence prevention organizations in the United States. The results centered on three themes: (1) Young people's journeys of gaining awareness of structural racism through personal experience with gun violence, (2) media's perpetuation of structural racism through its dismissal of community gun violence, and (3) the need for community‐based solutions to address the root causes of gun violence. These findings shed light on how societal elements, including the media, policymakers, and white‐led gun violence prevention organizations, perpetuate structural racism and pose challenges to the organizing efforts of Black and Latine youth. Furthermore, these findings amplify young Black and Latine gun violence prevention organizers' experiences with gun violence and their frustrations towards the discriminatory media portrayals of gun violence in their communities, as well as recognize the importance of their organizing work. Highlights: Black and Latine youth organizers' voices are important for understanding gun violenceMedia's harmful dismissal of community gun violence is a symptom of structural racism.Community‐based solutions are important to addressing to community gun violence.